Regional deprivation is associated with the distribution of vulnerable asylum seekers: a nationwide small area analysis in Germany - Bozorgmehr, Kayvan; Szecsenyi, Joachim; Stock, Christian (Journal of epidemiology and community health, 2017)
Background Newly arriving asylum seekers in many European Union countries are assigned a place of residence based on administrative quota. This may have important consequences for the exposure to contextual health risks. We assessed the association between regional deprivation and the distribution of asylum seekers in Germany considered as vulnerable (women, children <7 years, persons >64 years) because of their increased health needs. Methods Using nationally representative data, we analysed the rates of observed to expected numbers of asylum seekers and vulnerable subgroups in Bayesian spatial models. Regional deprivation was measured by the German Index of Multiple Deprivation. The analyses were performed at the district level (N=402) and adjusted for district population size, effects of federal states as well as spatial effects. Results Of the 224 993 asylum seekers, 38.7% were women, 13.8% children aged <7 years and 19.8% aged >64 years. The adjusted number of asylum seekers (totals and vulnerable subgroups) was higher in more deprived districts (Q3, Q4 and Q5) relative to districts in the lowest deprivation quintile (Q1). The adjusted rate ratios for districts with highest relative to those with lowest deprivation were 1.26 (1.03-1.53) for women, 1.28 (1.04-1.58) for children aged <7 years and 1.50 (1.08-2.08) for older asylum seekers. Conclusion The adjusted number of vulnerable asylum seekers was higher in districts with medium and highest deprivation compared with districts with lowest deprivation. The disproportionate distribution was highest for older asylum seekers and children <7 years. Vulnerable subgroups tend to be exposed to more deprived places of residence, which may further increase health risks and healthcare needs.